The Effect of Flexible Working Arrangements on Employee Performance: A Survey in Multi-Brand Virtual Kitchen Companies - Safira Aulia Khoirunnisa; Iwan Sukoco; Lina Auliana (Universitas Pendidikan Indonesia, 2025)
This study investigates the impact of competency and career The implementation of flexible working arrangements allows for adjustments to work patterns according to individual needs, which impacts performance. Flexible working arrangement at multi-brand virtual kitchen company has been applied but there is still no evidence that the implementation has significantly improved employee performance. This research aims to analyze the influence of flexible working arrangements on employee performance at a multi-brand virtual kitchen company. This study uses a quantitative method with a descriptive-verificative approach. Data was obtained through observation, interviews, and surveys via Google Form. The research sample consisted of 54 employees at the headquarters (HQ) of a multi-brand virtual kitchen company, selected using purposive sampling according to criteria. The data analysis used was hypothesis testing and simple linear regression analysis using SPSS software to carry out data analysis. The study results indicate that flexible working arrangements significant positively effect on the performance of employees at multi-brand virtual kitchens. These findings indicate that HQ employees at multi-brand virtual kitchen who work with flexible working arrangements show better performance.